E-Commerce Performance. Shopping Cart Key Performance Indicators - MUNTEAN, Mihaela I.; TARNAVEANU, Diana; ION, Ana Raluca (Informatica Economica, 2016)
In an e-commerce performance framework is important to identify the key performance indicators that measure success and together provide the greatest context into the business performance. Shopping carts are an essential part of ecommerce, a minimal set of key performance indicators being the subject of our debate. The theoretical approach is sustained by a case study, an e-shop implemented using PHP and MySQL, for simulating main business processes within the considered performance framework. Our approach opens a perspective for future research using additional indicators in order to properly evaluate the global performance of any e-shop.